Research on Risk Evaluation of Internet Strategic Transformation of Manufacturing Enterprises Based on the BP Artificial Neural Network - Honglei, Huang; Zaigham, Ghulam Hussain Khan (Frontiers in Psychology, 2022)
For manufacturing enterprises to successfully enter the “Industry 4.0” era and establish advantages in the new wave of the Industrial Revolution, they must use Internet thinking to transform manufacturing enterprises and promote the in-depth integration of informatization and industrialization under the premise of managing and controlling risks, to achieve transformation and upgrading. Research on and management of the risks of manufacturing enterprises’ Internet strategic transformation directly affects the success or failure of enterprises’ transformation. This study constructed a risk evaluation model for a manufacturing enterprise’s Internet strategic transformation based on the back propagation (BP) artificial neural network and conducted a case study on one enterprise.